Estudo da translocação de fósforo em cafeeiro pela utilização de radioisótopo - Dias, Luiz Eduardo; de Moura Estevão, Márcio; Alvarez V, Victor Hugo; A Monteiro da Silva, Eldo; Ferreira de Novais, Roberto; Braga, José Mário (Revista Ceres, 2025)
A well-defined compartmentalization of phosphorus was observed in coffee seedlings when only root of the radicular system of the plant was used to absorb 32p, This compartmentalization was manifest in the differential accumulation of radioisotopic activity in alternate leaves on the stem. A large 32p accumulation was observed in the apical leaf pair as well as in the treated root. The similarity of these results with those obtained with eosina-Y stain absorption suggests that the translocation pathways are the same in both cases.